Ionic Liquid Sheath Stabilizes Atomically Dispersed Reduced Graphene Aerogel‐Supported Iridium Complexes during Ethylene Hydrogenation Catalysis. Issue 19 (30th August 2022) - Kurtoğlu‐Öztulum, Samira F.; Yalçın, Kaan; Hoffman, Adam S.; Jalal, Ahsan; Zhao, Yuxin; Gates, Bruce C.; Bare, Simon R.; Unal, Ugur; Uzun, Alper
Abstract: An atomically dispersed reduced graphene aerogel (rGA)‐supported iridium catalyst having reactive ethylene ligands was synthesized at an iridium loading of 9.9 wt % and coated with an ionic liquid, 1‐ethyl‐3‐methylimidazolium acetate ([EMIM][OAc]). Continuous‐scan X‐ray absorption spectra demonstrated that the iridium remained site‐isolated in flowing equimolar C2 H4 and H2 during a temperature ramp to 100 °C. The data further showed the lack of detectable iridium aggregation when the feed was H2 ‐rich or even pure H2 at 100 °C. An Arrhenius plot determined for ethylene hydrogenation catalysis with the sample in flowing equimolar ethylene and hydrogen showed no variation in the apparent activation energy at temperatures up to 100 °C, confirming that the active sites remained intact at the higher temperatures. The results point to opportunities for overcoming the stability limitations of atomically dispersed supported noble metal catalysts by choice of electron‐donor supports and ionic liquid sheaths. Abstract : Supported Catalysts : An atomically dispersed reduced graphene aerogel (rGA)‐supported iridium catalyst having reactive ethylene ligands was synthesized at an iridium loading of 9.9 wt % and coated with an ionic liquid (IL), 1‐ethyl‐3‐methylimidazolium acetate ([EMIM][OAc]). Data demonstrate that electron donation by the IL sheath in combination with that of the rGA support hindered the aggregation of atomically dispersed Ir under harsh reaction conditions.